Netflix : pricing decision 2011 - Robinson, David; Oltersdorf, Max (London : SAGE Publications Ltd, 2017)
Beginning in 2007, Netflix began offering existing mail rental subscribers the opportunity to view a limited number of movies through internet streaming and no additional fee. This "free streaming" continued until mid-2011 when Netflix announced a split to their business with separate monthly fees (and separate websites and names) for streaming and mail disk subscriptions. The resulting customer backlash and threatened defections caused the company's stock price to drop 60 percent. As movie studios (the owners of the content) saw sales of DVDs drop, they began to sharply raise their prices for online content. Moreover, Netflix which had been dominant in the mail disk rental model began to face substantial competition from other streaming video providers. The case study provides students with an opportunity learn about pricing and to develop a pricing strategy for Netflix.
Originally published in Robinson, D., & Oltersdorf, M. (2013). Netflix: Pricing decision 2011. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Netflix (Firm); Consumer behavior -- Case studies; Pricing -- Case studies; Marketing -- Case studies; Motion pictures -- Distribution -- Case studies